HUBUNGAN KETERSEDIAAN BUKU BACAAN DENGAN MINAT BACA SISWA KELAS V SDN PASIRLAJA 01 - Triarsuci, Damara; Maksum , Arifin; Aruwiyantoko, Anggit (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is a relationship between the availability of reading books and the reading interest of fifth grade students of SDN Pasirlaja 01. The research method used is quantitative with simple correlation research. The population of this study was all fifth grade students of SDN Pasirlaja 01. The sample of this study was the entire population of 38 students or using a population study. The research instrument was a closed questionnaire. The data analysis technique used in this study was product moment. The results of this study indicate that there is a significant relationship between the availability of reading books and the reading interest of fifth grade students of SDN Pasirlaja 01. This can be seen from the results of the product moment test with a significant value of 0.000 <α = 0.05. In addition, the availability of reading books has a strong relationship with students' reading interest as indicated by a correlation value of 0.560 which indicates the degree of relationship between the basic literacy variable and the reading interest variable of 56.0%. Then the availability of reading books has a positive relationship with reading interest. This means that the better the availability of reading books, the better the reading interest of students.